Suitability and characteristics of rocks for sensible heat storage in CSP plants - Radia, AIT EL CADI (2022)
High temperature thermal energy storage (TES) is a crucial technology ensuring continuous generation of power from solar energy and plays a major role in the industrial field. Choosing the optimal storage material remains a great challenge. From the literature, it is understood that the natural rock is a good suitable material for TES in concentrating solar power (CSP) plants. However, not much work has been published on the behavior of rock and its suitability for TES. This paper evaluates the potential of rocks as candidate materials for use in high temperature thermal storage. On one hand, we provide literatures on sensible heat storage (SHS) materials and works carried out on packed rock beds, and on the other hand, experimental tests are conducted and data are analyzed and discussed in order to choose the best rocks among fifty two varieties. According to various criteria, the obtained results show that dolerite, granodiorite, hornfels, gabbro and quartzitic sandstone are the good candidates to be used as storage materials for air-based solar systems.